2022
DOI: 10.18332/tid/152221
|View full text |Cite
|
Sign up to set email alerts
|

The association between cotinine-measured smoking intensity and sleep quality

Abstract: INTRODUCTION Cigarette smoking is suggested to be associated with sleep problems. This study evaluated the quantitative association between urinary cotinine-verified smoking intensity and sleep quality assessed by the Pittsburgh Sleep Quality Index (PSQI). METHODS This was a cross-sectional study of 189970 participants from the Kangbuk Samsung Health Study recruited between 2016 and 2018. Logistic regression analysis adjusted for covariates was performed to estimate the association between urinary cotinine le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…It is well established that smokers have poorer sleep quality than nonsmokers (Liao et al, 2019;Oh et al, 2022). Current findings strengthened that night time smoking habit significantly increases the risk of poor sleep quality of desk-based officials compared to individuals those does not have night time smoking habit.…”
Section: Discussionmentioning
confidence: 52%
“…It is well established that smokers have poorer sleep quality than nonsmokers (Liao et al, 2019;Oh et al, 2022). Current findings strengthened that night time smoking habit significantly increases the risk of poor sleep quality of desk-based officials compared to individuals those does not have night time smoking habit.…”
Section: Discussionmentioning
confidence: 52%
“…In addition, our study found that both genders had the same urinary cotinine metabolite concentration, in contrast to a previous study that found higher concentrations in males than in females 37 . Our findings showed that those with lower education level than elementary school and aged >37 years showed higher urinary cotinine metabolite level, which might be important risk factors for smoking 38 . Moreover, this study found that those who were unemployed, used conventional cigarettes, and smoked ≥10 cigarettes per day showed higher urinary cotinine metabolite levels.…”
Section: Comparison Between Urinary Cotinine Metabolite and Character...mentioning
confidence: 55%
“…Smoking might affect renal function by causing chronic endothelial dysfunction, oxidative stress, and hardening of the glomeruli [44][45][46] . Moreover, exposure to passive smoking has been reported to be associated with significantly increased lipid peroxidation in the liver, increased catalase activity in the kidney, cardiac and blood vessel diseases, abnormal renal blood flow, and renal afflictions over time 38 . However, a few studies have identified a non-linear relationship between smoking and renal function in different populations through stratified analysis 22 .…”
Section: Correlation Between Urinary Cotinine Metabolite and Serum Eg...mentioning
confidence: 99%
“…Excessive production of ROS can cause hyperthyroidism, often accompanied by low TSH, high FT3, and FT4 [ 44 ]. Many articles studying smoking usually use cotinine as a surrogate quantitative measure to illustrate the strong correlation between the two [ 45 , 46 ]. In the present study, smoking data were used as a proxy because GWAS data for cotinine were not available.…”
Section: Discussionmentioning
confidence: 99%